Inexact Two-Grid Methods for Eigenvalue Problems (Journal of Computational Mathematics, 2021)
We discuss the inexact two-grid methods for solving eigenvalue problems, including both partial differential and integral equations. Instead of solving the linear system exactly in both traditional two-grid and accelerated two-grid method, we point out that it is enough to apply an inexact solver to the fine grid problems, which will cut down the computational cost. Different stopping criteria for both methods are developed for keeping the optimality of the resulting solution. Numerical examples are provided to verify our theoretical analyses.
Keywords: Inexact; Two-grid; Eigenvalue; Eigenvector; Finite element method; Convergence rate.